Therapeutic Strategies of Primary Molar Infraocclusion: A Systematic Review - Assunta Patano; Angelo Michele Inchingolo; Claudia Laudadio; Daniela Azzollini; Grazia Marinelli; Sabino Ceci; Giulia Latini; Biagio Rapone; Alessio Danilo Inchingolo; Antonio Mancini; Francesco Inchingolo; Daniela Di Venere; et al. (Children, 2023)
Background: Infraocclusion of deciduous molars is a clinical disturbance that occurs during primary and mixed dentition and has some orthodontic implications. Infraoccluded teeth are believed to be potential sites of malocclusion, with a risk of tipping neighbouring teeth and losing space. This systematic review aims to analyse the management of primary molars infraocclusion and to provide updated guidelines. Methods: A literature search was performed using PubMed, Scopus, and Web of Science databases from 1 January 2017 to 28 November 2022. The inclusion criteria were: studies only on human subjects, open access studies, case reports, randomised trials, retrospective, observational studies, and English language. Results: A total of 372 publications were identified from the databases and a final number of nine studies were included in the review for qualitative analysis. Conclusion: Management of patients suffering from infraocclusion depends on the severity, age at diagnosis, and presence of succeeded premolars. Early diagnosis of infraoccluded primary elements is fundamental and cannot be postponed. Preservation of the primary molars may be a valid option with long-term stability if there is no or moderate primary molar infraocclusion, root resorption of less than half of the root, and no decay or restoration.